The effect of oxytocin massage on increasing breast milk production in breastfeeding mothers: Oxytocin Massage - Ramadhani Syafitri Nasution; Yuniati Yuniati; Elya Rosa br Sembiring (Institute of Computer Science (IOCS), 2023)
Breastfeeding is a scientific process, but mothers often fail or stop breastfeeding prematurely. Breast milk is a white liquid produced by the mother's breast glands through the breastfeeding process. For mothers who breastfeed, smooth milk is very important to meet the needs of the baby. This study aims to determine the effect of oxytocin massage on increasing milk production for breastfeeding mothers at the Siti Kholijah HSB Medan Pratama Clinic in 2022. This type of research is a quasi-experimental technique (Quasi Experiment) with pretest and posttest without control group, namely a research design using observation before and after experiment. The research location was at the Siti Kholijah Hsb Medan Pratama Clinic on Jl. Marelan I West IV Market, Waterfall Village, Medan Marelan District. The population in this study were 15 people and a sample of 15 people in breastfeeding mothers. Data were analyzed using the T test. The results showed that the statistical test using the T test, the calculation results obtained p value = 0.000 <0.05, meaning that there is a difference before being given treatment and after being given treatment. The conclusion in this study is for health workers in the Waterfall sub-district to hold counseling which aims to increase public knowledge, especially about oxytocin massage, which can increase milk production and provide exclusive breastfeeding.